Improved practices for forest management and fish smoking in Cameroon’s mangroves - Awono, A.; Ntamag-Ndjebet, C.N.; Schure, J.; Ihalainen, Markus; Zobo, J.; Tieminie, R.; Mama, M.N.; Mengue, P.; Ngo Nken, I.; Tankeu, E.; Essamba, L.F.; Sonwa, D.J.; et al. (CIFOR-ICRAF, 2023)
Mangrove forests, which serve as breeding grounds for fish and crustacea, contribute to livelihoods of communities living on Manoka Island in Cameroon. In the absence of sustainable management mechanisms, these same mangrove forests and livelihoods are under pressure due to overharvesting of wood for fish smoking.